2016
DOI: 10.5860/crl.77.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Success: Open Access Policies at North American Educational Institutions

Abstract: © 2016 Christine Fruin and Shan Sutton, Attribution-NonCommercial (http://creativecommons. org/licenses/by-nc/3.0/) CC BY-NC. Recognizing the paucity of quantitative and qualitative data from North American educational institutions that have pursued open access policies, the authors devised a survey to collect information on the characteristics of these institutions, as well as the elements of the open access policies, the methods of promoting these policies, faculty concerns about the policies, and how those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 5 publications
0
29
1
Order By: Relevance
“…The policy applies to all URI faculty and stipulates that "each Faculty member will provide an electronic copy of the author's final version of each article no later than the date of its publication… to the University Libraries" and that the University Libraries may "make the article available to the public in an open-access repository" (University of Rhode Island Faculty Senate, 2013). While designed as a mandate, these types of OA policies are optional in practice due to the presence of a waiver provision and lack of any penalties for non-compliance (Anderson, 2016;Basken, 2016;Fruin & Sutton, 2016;Shieber, 2009;Smith, 2012; Suber, 2012;Zhang, Boock, & Wirth, 2015).At URI, faculty members are encouraged and expected to share the author manuscript version of their articles through the IR under the terms of the OA Policy. Unlike other institutions that have developed procedures to harvest articles from open sources and publishers by agreement (Duranceau & Kriegsman, 2013;Duranceau & Kriegsman, 2015;Fruin & Sutton, 2016;Kilcer, 2015;Kipphut-Smith, 2014a;Kipphut-Smith, 2014b;Smith, 2012), URI has implemented a mostly manual workflow that relies on active faculty participation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The policy applies to all URI faculty and stipulates that "each Faculty member will provide an electronic copy of the author's final version of each article no later than the date of its publication… to the University Libraries" and that the University Libraries may "make the article available to the public in an open-access repository" (University of Rhode Island Faculty Senate, 2013). While designed as a mandate, these types of OA policies are optional in practice due to the presence of a waiver provision and lack of any penalties for non-compliance (Anderson, 2016;Basken, 2016;Fruin & Sutton, 2016;Shieber, 2009;Smith, 2012; Suber, 2012;Zhang, Boock, & Wirth, 2015).At URI, faculty members are encouraged and expected to share the author manuscript version of their articles through the IR under the terms of the OA Policy. Unlike other institutions that have developed procedures to harvest articles from open sources and publishers by agreement (Duranceau & Kriegsman, 2013;Duranceau & Kriegsman, 2015;Fruin & Sutton, 2016;Kilcer, 2015;Kipphut-Smith, 2014a;Kipphut-Smith, 2014b;Smith, 2012), URI has implemented a mostly manual workflow that relies on active faculty participation.…”
mentioning
confidence: 99%
“…While designed as a mandate, these types of OA policies are optional in practice due to the presence of a waiver provision and lack of any penalties for non-compliance (Anderson, 2016;Basken, 2016;Fruin & Sutton, 2016;Shieber, 2009;Smith, 2012; Suber, 2012;Zhang, Boock, & Wirth, 2015).…”
mentioning
confidence: 99%
“…The principal concern is that, to allay academics' fears around the loss of academic freedom, they are given the right to opt out of the mandate on a case by case basis. A recent survey by Fruin and Sutton (2016) of US universities who had either 'enacted' an open access policy or had a policy 'in process' found that "most policies (86 percent in the Enacted Policy Group and 67 percent in the In Process Group) include language that grants automatic waivers to a faculty author on request without justification or explanation." These waivers may result in an embargo period being placed on the paper, or if the academic or publisher demands it, the paper not being made available at all.…”
Section: University Open Access Policies and Mandatesmentioning
confidence: 99%
“…However, individual academics would still have the right to opt-out of the licence if their publisher of choice does not accept the UK-SCL terms. This will need to be monitored if the UK is to avoid the situation facing the 70% of US universities who find themselves honouring publisher embargoes as a result of 87% of their policies allowing opt-outs (Fruin and Sutton, 2016). In such cases, academics may find themselves negotiating either with the publisher for a (reduced) embargo period, or with their institution to get a waiver.…”
Section: Number Of Policiesmentioning
confidence: 99%
See 1 more Smart Citation